Time from diagnosis to treatment of colorectal cancer in a South Australian clinical registry cohort: how it varies and relates to survival. Issue 9 (30th September 2019) - Roder, David; Karapetis, Christos Stelios; Olver, Ian; Keefe, Dorothy; Padbury, Robert; Moore, James; Joshi, Rohit; Wattchow, David; Worthley, Dan L; Miller, Caroline Louise; Holden, Carol; Buckley, Elizabeth; et al.
Abstract : Objectives: Some early studies indicated lower survival with longer time from diagnosis to cancer treatment, but others showed the reverse. We investigated time to treatment of colorectal cancer and associations with survival. Setting and participants: Clinical registry data for colorectal cancer cases diagnosed in 2000–2010 at four major public hospitals in South Australia and treated by surgery (n=1675), radiotherapy (n=616) and/or systemic therapy (n=1556). Design: A historic cohort design, with rank-order tests for ordinal clinical and sociodemographic predictors and multiple logistic regression for comparing time from diagnosis to treatment. Unadjusted Kaplan-Meier estimates and adjusted Cox proportional hazards regression were used to investigate disease-specific survival by time to treatment. Outcome measures: Time to treatment and survival from diagnosis to death from colorectal cancer. Results: Treatment (any type) commenced for 87% of surgical cases < 60 days of diagnosis, with 80% having surgery within this period. Of those receiving radiotherapy, 59% began this treatment < 60 days, and of those receiving systemic therapy, the corresponding proportion was 56%. Adjusted analyses showed treatment delay >60 days was more likely for rectal cancers, 2006–2010 diagnoses, residents of northern than other metropolitan regions and for surgery, younger ages <50 years and unexpectedly, those residing closer to metropolitan services. Adjusting for clinical and sociodemographic factors, and diagnostic year, better survival occurred in < 2 years from diagnosis for time to treatment >30 days. Survival in the 3–10 years postdiagnosis generally did not differ by time to treatment, except for lower survival for any treatment >90 days for surgical cases. Conclusions: The lower survival < 2 years from diagnosis for treatment < 30 days of diagnosis is consistent with other studies attributed to preferencing more complicated cases for earlier care. Lower 3–10 years survival for surgical cases first treated >90 days from diagnosis is consistent with previously reported U-shaped relationships.